Laser Welding Applied to Complex Phase Steel - Dias, Erica Ximenes [UNESP]; Reis De Faria Neto, Antonio [UNESP]; Castro, Thais Santos [UNESP]; Martins, Marcelo Sampaio [UNESP]; Santos Pereira, Marcelo [UNESP] (SAE International, 2024)
The development of advanced high-strength steels has become essential in the production of lightweight, safe, and more economical vehicles within the context of the automotive industry. Among the advanced high-strength steels, complex phase steels stand out, characterized by their high formability and high energy absorption and deformation capacity. Laser welding is a technique that applies laser using high energy density as a heat source. It has the advantages that the high welding speed and low heat input compared to other welding methods cause a decrease in deformation, and the narrow width of the weld bead and heat-affected zone allows for the welding of complex parts that would be difficult for other welding methods. Based on a study of a complex phase steel, an analysis was made of the microstructures observed by optical microscopy, the grain boundaries and certain phases contained in this microstructure, as well as the microstructures of each area in the laser welding region observed by scanning electron microscopy. Presenting as results the microstructures of the welded region, such as martensite and bainite phases are the dark phases and retained austenite and ferrite phases are the light phases.